Stocks and shares - Millard, Brian J. (John Wiley, 1998)
This text aims to show how the elements of risk involved in decision-making - when to buy or sell, which shares to choose, which rumours to heed and which newspaper reports to believe - can be minimized by timing decisions to exploit market trends fully.